Forensic Physchiatry in Turkish Republic of Northern Cyprus Three Case Reports - Çakıcı, Mehmet; Tansel, Ebru; Ataklı, Cem; Polat, Oğuz (The Bulletin of Legal Medicine, 1996)
In our study three cases were discussed with in chapter 154 of Criminal Law and chapter 155 of Criminal Procedure Law of Turkish Republic of Northern Cyprus. Between 1971- 1994, the court sent 11 cases to the Lefkoşa Barış Mental Health Hospital to determine whether they have the competency to stand trial and criminal responsibility. Hospital documents showed that 3 mental patients who had homicidal acts had been charged according to the chapter 154 as incompetent, and they had been detayed in a criminal mental hospital for any period determined by Council of Ministry according to the chapter 155. In the light of these 3 cases, each having had severe homicidal acts, law relating to the mental patients in Turkish Republic of Northern Cyprus with the custody and maintenance of these patients for the purpose of public safety were discussed. Key words: Forensic Psychiatry, Law, Dangerousness